Соціолінгвістичні передумови розвитку банківської термінології в англійській мові - Тягур, Ю.В. (Центр наукових досліджень та викладання іноземних мов НАН України, 2009)
The paper deals with the socio-cultural background of English banking terminology. The term is postulated to be a lexical and semantic complex able to verbalize both special and abstract notions. Being derived from Old Greek and Latin at present English banking terminology has become a universal language of banking.